Peran Mahasiswa KKN UNP Dalam Menjaga Tradisi Keagamaan di Jorong Taratak Baru Kabupaten Solok - Fitra, Halkadri; Callista Nabilah, Shafira; Gustina, Puspita; Zasabila, Dilla; Ulal Zilfarid, Maf; Ferdiansya, Ferdiansya (Universitas Negeri Padang, 2025)
Religious traditions are an integral part of community life, especially in areas that strongly uphold cultural values and customs. However, modernization and globalization have led to a decline in youth participation in religious activities. This study aims to examine the role of Universitas Negeri Padang (UNP) community service program (KKN) students in preserving religious traditions in Jorong Taratak Baru. The research employs a qualitative approach through field observations and participation in community activities. The findings reveal that KKN UNP students play a crucial role in enhancing community engagement in religious traditions through various activities such as teaching Quran recitation, communal work at places of worship, and organizing Isra’ Mi’raj celebrations. The active participation of students not only strengthens social bonds among residents but also serves as a medium for transmitting religious values to younger generations. Therefore, the KKN program has significant potential in sustaining religious traditions amidst ongoing social changes